Governance, Sustainability And The New Zealand Small To Medium Enterprise Sector - M. Daud Ahmed; John Horsley; Wan Norisma Wan Ismail (Common Ground Research Networks, 2024)
The interface between governance and sustainability is the subject of increasing scrutiny. Much of the analysis focuses on state-based frameworks and market prototypes, with a focus on models for large enterprises. In New Zealand, 97% of enterprises are small to medium enterprises (SMEs), defined as firms with 19 or fewer employees, contributing 40% of the economy's total output. The SME focus is primarily centred on profitability. To date, there has been sporadic attention given to the interaction of economic, social and environmental impacts of this sector, and to the governance frameworks that support sustainability models and practices. An effective governance and sustainability framework for SMEs has significant implications for the country. This research identifies the links between governance and sustainability, and the practices currently operating in New Zealand SMEs. The paper presents a prescriptive model for practicing governance which seeks to achieve a workable sustainability model for SMEs.